Peningkatan Keterampilan Pemetaan Pikiran (Mind Mapping) dalam Pembelajaran IPS untuk Meningkatkan Pemahaman Siswa Kelas VIII di SMP Negeri 1 Geneng Tahun Pelajaran 2024 / 2025: Penelitian - Yuanita Gusni; Ninik Srijani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research was conducted in class VIII of SMP Negeri 1 Geneng. The purpose and objectives to be achieved in the study were to improve the completeness of student learning outcomes and student activities in learning activities by applying the Mind Mapping method. There were 18 female students and 12 male students out of a total of 30 students who were the subjects of the study. This study used 2 cycles and four stages, namely planning, implementation, observation / observation and reflection. Mind Mapping is a visual method for organizing ideas and information. It uses diagrams with the main concept in the middle and branches representing related ideas. This technique helps to understand, remember, and connect concepts effectively. The end of this abstract can be taken as a result in the implementation of class research will be known the interests and readiness of students before the research is conducted, after the classroom action research using the Mind Mapping system is conducted can improve memory, critical thinking skills, and interest in learning. By organizing information visually mind mapping helps students to understand concepts better and facilitates understanding of learning materials